Seigniorage, banking, and the optimal quantity of money - Baltensperger, Ernst; Jordan, Thomas J. (Journal of Banking & Finance, 1997)
This paper discusses seigniorage in an economy with imperfect competition in the banking sector. The amount of total seigniorage and its division between the central bank and the banking sector are derived by using the opportunity cost concept of seigniorage. The paper analyzes the impact of changes in inflation, reserve requirements, competition and technology on the division of seigniorage and on the welfare loss and relates the analysis to the concept of the optimal quantity of money.